2005
DOI: 10.1007/s10712-005-1882-4
|View full text |Cite
|
Sign up to set email alerts
|

Coupling the Solar-Wind/IMF to the Ionosphere Through the High Latitude CUSPS

Abstract: Magnetic merging is a primary means for coupling energy from the solar wind into the magnetosphere-ionosphere system. The location and nature of the process remain as open questions. By correlating measurements from diverse locations and using large-scale MHD models to put the measurements in context, it is possible to constrain our interpretations of the global and meso-scale dynamics of magnetic merging. Recent evidence demonstrates that merging often occurs at high latitudes in the vicinity of the cusps. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…Savin et al (2002a) accounted for the difference of the power for Polar and Interball spectra of about one order of magnitude by the average magnetic field annihilation in a patchy reconnection (cf. Maynard, 2003). Similar reasoning for 29 May 1996 has been proposed by Savin et al (2004).…”
Section: Turbulent Boundary Layer and Multiscale Reconnectionsupporting
confidence: 68%
See 2 more Smart Citations
“…Savin et al (2002a) accounted for the difference of the power for Polar and Interball spectra of about one order of magnitude by the average magnetic field annihilation in a patchy reconnection (cf. Maynard, 2003). Similar reasoning for 29 May 1996 has been proposed by Savin et al (2004).…”
Section: Turbulent Boundary Layer and Multiscale Reconnectionsupporting
confidence: 68%
“…Savin et al (1998bSavin et al ( , 2001Savin et al ( , 2002aSavin et al ( , b, 2004 and Maynard (2003) provide relevant references and results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such cases magnetic mapping between merging sites and the conjugate northern and southern cusps remains intelligible, albeit more complicated. However, the temporal and spatial properties of energetic electron tails are similar (Maynard et al, 2005). Cowley and Lockwood (1992) suggested that merging is intermittent, occurring in bursts, separated by quiescent gaps at particular locations.…”
mentioning
confidence: 90%
“…Particle measurements acquired during a fortuitous DMSP overflight of an auroral structure above Svalbard showed that electrons with energies between 0.5 and a few keV were the sources of 557.7 nm emissions. Maynard et al (2005) used Polar data to show that electrons with similar energies constitute the high-energy tails of the suprathermal electron distributions found on field lines connected to active merging sites.…”
mentioning
confidence: 99%